Internet and decision-making regarding health among pregnant woman: cross-cultural adaptation of a questionnaire for use in Brazil - Ana Carolina Cleto Borges; Raquel Conceição Ferreira; Lorrany Gabriela Rodrigues; Matheus França Perazzo; Saul Martins Paiva; Maria Inês Barreiros Senna (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
The aim of this study was to translate and cross-culturally adapt the Women's Use of the Internet in Pregnancy Questionnaire (WUIPQ) to Brazilian Portuguese and analyze the psychometric properties of the Preparation for Decision Making Scale (PDMS). This study consisted of the following steps: translation, synthesis, back-translation, evaluation by the author of the original questionnaire, review by the panel of experts, and pretest of the WUIPQ. For such, Brazilian pregnant women and mothers who were members of Facebook groups participated in the study. We measured test-retest reliability as well as internal consistency and performed confirmatory factor analysis (CFA) of the B-PDMS. In the pretest, 88.14% of the participants considered the items of the B-WUIPQ to be clear and pertinent, and 84.09% rated the sequence and organization of the questionnaire as excellent/good. The intraclass correlation coefficient and Cronbach's alpha coefficient for the B-PDMS were 0.850 (95%CI: 0.791-0.899) and 0.91, respectively. CFA revealed factor loadings higher than 0.70 for most items, with a comparative fit index of 0.989, Tucker-Lewis index of 0.984, and root mean square error of approximation of 0.08 (95%CI: 0.06-0.09). The B-WUIPQ presented cross-cultural adapted, and the B-PDMS demonstrated satisfactory psychometric proprieties to Brazilian pregnant women.